CHEMICAL EQUILIBRIUM MODEL OF SOLUTION BEHAVIOR AND SOLUBILITY IN THE H-NA-K-OH-CL-HSO4-SO4-H2O SYSTEM TO HIGH CONCENTRATION AND TEMPERATURE - Christov C.; Moller N. (My University, 2004)
This paper describes a chemical model that calculates solute and solvent activities and solid-liquid equilibria in the H-Na-K-OH-Cl-HSO4-SO4-H2O system from dilute to high solution concentration within the 0° to 250°C temperature range. All binary and ternary subsystems are included in the model parameterization. The model is validated by comparing predictions with experimental data, primarily in higher order systems, not used in the parameterization process. Limitations of the model due to data insufficiencies are discussed.The Harvie and Weare (GCA44, 981, 1980) solubility modeling approach, incorporating their implementation of the concentration-dependent specific interaction equations of Pitzer (J. Phys. Chem.77, 268, 1973), is employed. This model expands the variable temperature Na-K-Cl-SO4-H2O model of Greenberg and Moller (GCA53, 2503, 1989) by including acid (H2SO4, HCl) and base (NaOH, KOH) species. Temperature functions for the chemical potentials of 5 acidic (sodium bisulfate, sodium sesquisulfate, mercallite, potassium sesquisulfate and misenite) and 6 basic (4 sodium hydroxide hydrates and 2 potassium hydroxide hydrates) solid phases are determined.